EFEKTIVITAS PENGAWASAN KOMISI YUDISIAL PENGHUBUNG WILAYAH RIAU TERHADAP PENEGAKAN KODE ETIK HAKIM DI PENGADILAN NEGERI PEKANBARU TAHUN 2021 - muhammad roif alghani; Dodi Haryono; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Judicial Commission Liaison (PKY) is an institution that assists the tasksof the Indonesian Judicial Commission in the regions. PKY Riau Region wasformed in 2013, according to Judicial Commission Regulation Number 1 of 2012concerning the Establishment, Structure and Liaison Work Procedures forRegional Judicial Commissions, its performance has not been optimal in carryingout its duties and functions.The method used study is an empirical juridicalapproach or legal sociology. The author conducted direct research at theresearch locations at the Riau Region PKY Office and the Pekanbaru DistrictCourt. The sampling technique was total sampling. Primary data collection byinterviews, observation and documentation, while secondary data by way ofliterature study. Furthermore, all data is processed and studied using adescriptive analytical method that combines field data with library data.Theresults of the study show that the Riau Regional PKY in carrying out the task ofmaintaining the honor and nobility, dignity and behavior of judges is based onpublic reports while sanctions against judges for violations are the authority ofthe Indonesian Judicial Commission (central). There are several inhibiting factorsthat affect the performance of the Riau Region PKY in enforcing the Code ofEthics for Judges at the Pekanbaru District Court, including online trials, covid-19, lack of human resources, and limited authority. This causes the supervisioncarried out by the Riau Region PKY to enforce the Code of Ethics for Judges atthe Pekanbaru District Court in 2021 to be less effectiveKeywords: Judicial Commission, Judicial Commission Liaison, Enforcement ofthe Code of Ethics and Judges Code of Conduct,